2018
DOI: 10.3390/ijms19072043
|View full text |Cite
|
Sign up to set email alerts
|

Role of mTOR in Glucose and Lipid Metabolism

Abstract: The mammalian target of rapamycin, mTOR is the master regulator of a cell’s growth and metabolic state in response to nutrients, growth factors and many extracellular cues. Its dysregulation leads to a number of metabolic pathological conditions, including obesity and type 2 diabetes. Here, we review recent findings on the role of mTOR in major metabolic organs, such as adipose tissues, liver, muscle, pancreas and brain. And their potentials as the mTOR related pharmacological targets will be also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
195
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(209 citation statements)
references
References 97 publications
8
195
1
5
Order By: Relevance
“…For instance, excessive mTORC1 activity enhances lipogenesis by the induction of Sterol regulatory element-binding protein 1 (SREBP1c) [9][10][11][12]. Furthermore, mTORC1 activation suppresses peroxisome proliferator-activated receptor α (PPARα) activity, which in turn inhibits β-oxidation in the liver [13,14]. mTORC1 has been shown to suppress the autophagy pathway via regulation of autophagy activation kinase 1 (ULK1) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, excessive mTORC1 activity enhances lipogenesis by the induction of Sterol regulatory element-binding protein 1 (SREBP1c) [9][10][11][12]. Furthermore, mTORC1 activation suppresses peroxisome proliferator-activated receptor α (PPARα) activity, which in turn inhibits β-oxidation in the liver [13,14]. mTORC1 has been shown to suppress the autophagy pathway via regulation of autophagy activation kinase 1 (ULK1) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that many obese patients with disordered lipid metabolism have dysfunction of mTOR in the body, suggesting that mTOR is involved in lipid metabolism [49][50][51]. Studies have shown that mTOR can increase the expression of SREBPs in fat synthesis-related genes and promote the splicing modification of SREBPs in Golgi apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes. The roles of mTOR in glucose and lipid metabolism and diabetes have been extensively studied (57,58). Type 2 diabetes can be successfully induced in zebrafish by a daily high fat diet consisting of brine shrimp and 1% egg yolk for 10 weeks.…”
Section: The Role Of Ztor In Age-related Diseases In the Zebrafish Modelmentioning
confidence: 99%